2023
DOI: 10.1029/2022jg007140
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Increasing Ecosystem Water Limitation During the Past Three Decades in the Yellow River Basin, China

Abstract: Terrestrial ecosystems are essential for the provision of services for living organisms and CO 2 uptake. Changes in the state and functions of ecosystems can substantially impact human economic development (Denissen et al., 2022). Vegetation is key to the exchange of water, energy, and carbon between the land surface and atmosphere, transpiration through plant stomata plays an important role in terrestrial ecosystems (Gentine et al., 2019;Humphrey et al., 2021). Changes in vegetation are thus explicitly linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…For example, Wu et al (2018) and Wu et al (2022) both assessed drought legacy effects on vegetation. Zhao et al (2023) indicated that the ecosystem of a typical drylands was facing crucial water limitation in recent decades. Additionally, Wang et al (2021) investigated the changes in the length of the four seasons and their impact on vegetation in the drylands.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wu et al (2018) and Wu et al (2022) both assessed drought legacy effects on vegetation. Zhao et al (2023) indicated that the ecosystem of a typical drylands was facing crucial water limitation in recent decades. Additionally, Wang et al (2021) investigated the changes in the length of the four seasons and their impact on vegetation in the drylands.…”
Section: Introductionmentioning
confidence: 99%
“…Different land covers can have varying effects on SM (S. Wang et al, 2012); therefore, it can provide insights into the sensitivity of vegetation to SM. Also, our selection of these variables is informed by prior research (Jiao et al, 2021; F. Zhao et al, 2023) and combined with the specific context of the LP.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that the Qinghai-Tibet Plateau is at a high altitude, where the headwaters of the Yellow River is located, but it has warmed significantly in the past few decades (Li et al, 2010;Yang et al, 2014;Kuang and Jiao, 2016), and it is possible that the energy limitation in this area will be transformed into water limitation. However, Zhao et al (2023) showed that the headwaters of the Yellow River are still an energy-restricted area with increasing temperature. This research is generally consistent with our research conclusion, but there are differences in the spatial distribution, which may be caused by the poor simulation effect of the method and CMIP6 precipitation data.…”
Section: Uncertainty and Impactmentioning
confidence: 99%